PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM PROSES BELAJAR MENGAJAR SEKOLAH DASAR DI KABUPATEN MELAWI - Waridah Waridah; Aprima Tirsa (STKIP Melawi, 2022)
Abstract: The purposes of the study were to describe teacher pedagogic competence, improvement efforts, and to identify factors that influence the efforts to improve teacher’s pedagogic competence in the teaching and learning process in elementary schools in Melawi Regency. The type of research used qualitative descriptive research is that researchers observe and interact through interview activities. Data analysis was conducted by data reduction, data presentation (data display), and drawing conclusions (verification). The results of the study show that the pedagogical competence of teachers can be seen from the ability to understand students, make learning plans, carry out learning, evaluate learning outcomes, and develop students to actualize their various potentials properly. Efforts to improve pedagogic competence are by attending, training, training, upgrading, workshops, seminars/discussions, supervision, and regular meetings. The factors that influence the efforts to improve the pedagogical competence of teachers are: educational background, teaching experience, state of health, state of well-being, educational facilities, work discipline in schools, and supervision of the principal. Keywords: Pedagogic Competence, Teacher, Primary School Abstrak: Tujuan penelitian untuk mendeskripikan kompetensi pedagogik guru, upaya peningkatan, dan mengidentifikasi faktor yang mempengaruhi upaya peningkatan kompetensi pedagogik guru dalam proses belajar mengajar pada sekolah dasar di Kabupaten Melawi. Jenis penelitian yang digunakan penelitian deskriptif kualitatif yaitu peneliti mengamati dan berinteraksi melalui kegiatan wawancara. Analisis data dengan cara reduksi data (data reduction), penyajian data (data display), dan penarikan kesimpulan (verification). Hasil penelitian bahwa kompetensi pedagogik guru terlihat dari kemampuan dalam memahami peserta didik, membuat perencanaan pembelajaran, melaksanakan pembelajaran, mengevaluasi hasil belajar, dan mengembangkan peserta didik untuk mengaktualisasikan berbagai potensi yang dimilikinya dengan baik. Upaya peningkatan kompetensi pedagogik yaitu dengan mengikuti, pelatihan, diklat, penataran, lokakarya (workshop), seminar /diskusi, supervisi (pengawasan), dan pertemuan rutin. Adapun faktor-faktor yang mempengaruhi upaya peningkatan kompetensi pedagogik guru, yaitu: latar belakang pendidikan, pengalaman mengajar, keadaan kesehatan, keadaan kesejahteraan, sarana pendidikan, kedisiplinan kerja di sekolah, dan pengawasan kepala sekolah.Kata Kunci: Kompetensi Pedagogik, Guru, Sekolah Dasar